Filipino Work Values and Job Satisfaction among Teachers of Selected Elementary Schools in the Division of Zambales - Laurenio Jr, Welmer A.; Cabal, Esmen M. (Future Science / FSH-PH Publications, 2023)
The study investigates the relationship between work values and job satisfaction among teachers, aiming to understand how teachers' values influence their overall job satisfaction. Specifically, the focus is on Filipino work values among elementary school teachers in the Division of Zambales. A survey questionnaire was employed to assess the work values and job satisfaction of teacher-respondents. Results revealed a demographic profile of primarily female teachers in the early middle-aged group, married, Roman Catholic, Master's degree holders, with substantial teaching experience, occupying the position of Teacher I, and earning an entry-level monthly income. Filipino work values received high ratings, emphasizing their significance in shaping professional attitudes. Teacher-respondents expressed a high level of job satisfaction. Significant differences in Filipino work values were identified, including intellectual achievement orientation, interpersonal values, managerial values, material values, occupational values, religious values, organizational values, and variety values, based on various demographic factors. Similarly, significant differences in job satisfaction were noted concerning job security and job responsibilities. The study established a significant relationship between Filipino work values and job satisfaction among elementary teacher-respondents. Recommendations include a thorough evaluation of work values by the Human Resource Management (HRM) Office before employee promotion. Future research should expand the scope to validate and generalize findings, contributing to a more comprehensive understanding of Filipino work values and job satisfaction among teachers.